ANALYZING THE EFFECT OF FINANCIAL LITERACY ON THE SUCCESS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES): A CASE STUDY IN WEST JAVA - Marbun, Frederic Kornelius (Branding: Jurnal Manajemen dan Bisnis, 2024)
Financial literacy plays an important role in determining the sustainability and growth of Micro, Small, and Medium Enterprises (MSMEs). Many MSMEs face difficulties in managing their business finances due to a lack of understanding of financial recording, cash flow management, and investment planning. Limited access to financial education and limitations in adopting financial technology further exacerbate this condition, hampering the competitiveness and expansion of small businesses. This study aims to analyze the influence of financial literacy on the success of MSMEs in West Java and identify challenges and strategies for improving financial literacy among small and medium business actors. This study uses a qualitative approach by collecting data from various sources, such as previous research and study reports. The data obtained is analyzed systematically to identify patterns, relationships, and solutions that can improve the financial literacy capacity of MSMEs. The results of the study show that good financial literacy contributes to business stability through more effective cash flow management and more targeted investment strategies. Access to financing and an understanding of debt management are also important factors in supporting MSME growth. Therefore, improving financial literacy must be done through collaboration between the government, private sector, and academics to create a more sustainable business ecosystem for MSMEs.